Older People's Perceptions of Well-Being - I.V. Vasileva; M.V. Chumakov (Клиническая и специальная психология)
The study is aimed at identifying the structure and content of elderly people's ideas about well-being. The study involved 264 people aged 55 to 97 years (M = 69.54; SD = 6.98). Data collection method: free association method in the form of simple limited associations. Participants were asked to give associations to the word “well-being”. Nine associations were received from each person, three verbs, adjectives, nouns. Data processing was carried out using frequency analysis, rank calculation, z-criterion calculation to compare the frequencies of the identified associative and semantic groups. 2376 associates were received, of which the most frequent ones were identified; the selection boundary was 1% of the total number of associates (24 units). The most frequent ones were combined into 21 associative groups. Then the associative groups were combined into semantic groups (8) according to the principle of semantic enlargement. The obtained results allow us to say that well-being in the ideas of elderly people is health combined with emotions of calmness and happiness. In elderly people, the semantic group “emotions” belongs to the core ideas, and the associative group “health” belongs to the middle zone together with the groups “employment”, “material wealth”, “family”. At the same time, this does not indicate a lower significance of the associative group “health”, since the semantic group “emotions” collects its high rank only through a set of different emotions. The semantic groups “values", “existence”, “success” belong to the peripheral zone of ideas. In the semantic group “emotions” in the structure of ideas about well-being in elderly people, emotions of greater intensity prevail over emotions of lesser intensity. Markers of negative emotions in the structure of ideas about well-being are absent.